2016
DOI: 10.1248/bpb.b15-00730
|View full text |Cite
|
Sign up to set email alerts
|

β-Lapachone Regulates the Transforming Growth Factor-β–Smad Signaling Pathway Associated with Collagen Biosynthesis in Human Dermal Fibroblasts

Abstract: The transforming growth factor (TGF)-β-Smad signaling pathway regulates collagen biosynthesis in human dermal fibroblasts. We found that β-lapachone stimulated type I collagen expression in human dermal fibroblasts. In this study, we evaluated whether the β-lapachone-induced upregulation of collagen biosynthesis in human dermal fibroblasts is associated with the TGF-β-Smad signaling pathway. In cultured human dermal fibroblasts, both Smad 2 and Smad 3 (Smad 2/3) were phosphorylated by β-lapachone treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For instance, Smad binding element CAGACA located at −263 to −258 bp of the collagen type I alpha 2 (COL1A2) promoter is thought to be one of the most potent mediators of COL1A2 promoter activity in ventricular fibrosis and collagen synthesis (Masatoshi, 2010). Recently, transforming growth factor (TGF)‐β/Smad signalling pathway has emerged as a potential mediator of cell growth and differentiation, playing a critical role in the regulation of collagen synthesis (Park, Jeong, & Kim, 2016; Tang et al., 2011; Zhao, Shi, Dang, Zhai, & Ye, 2015). It has been reported that the autocrine TGF‐β signalling hypothesis can explain the intrinsic activation of collagen promoter in systemic sclerosis fibroblasts (Masatoshi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Smad binding element CAGACA located at −263 to −258 bp of the collagen type I alpha 2 (COL1A2) promoter is thought to be one of the most potent mediators of COL1A2 promoter activity in ventricular fibrosis and collagen synthesis (Masatoshi, 2010). Recently, transforming growth factor (TGF)‐β/Smad signalling pathway has emerged as a potential mediator of cell growth and differentiation, playing a critical role in the regulation of collagen synthesis (Park, Jeong, & Kim, 2016; Tang et al., 2011; Zhao, Shi, Dang, Zhai, & Ye, 2015). It has been reported that the autocrine TGF‐β signalling hypothesis can explain the intrinsic activation of collagen promoter in systemic sclerosis fibroblasts (Masatoshi, 2010).…”
Section: Introductionmentioning
confidence: 99%